INTEREST AND AWARENESS LEVELS OF THE TEACHER CANDIDATES FROM SİNOP UNIVERSITY ABOUT THE HISTORICAL AND CULTURAL MONUMENTS IN SİNOP - Kibar AKTIN (Fırat University, 2021)
This study was carried out in order to determine the interest and awareness levels of the teacher candidates, who are still studying at Sinop University, Faculty of Education, about the historical and cultural monuments located in Sinop. The study is a descriptive one using both of the qualitative and quantitative research methods. Target population of the study consists of the teacher candidates still studying at Sinop University, Faculty of Education in fall semester for the academic year of 2012-2013. The target population was formed with 328 teacher candidates studying at grade 2 and 3 by using the sampling method intended for the sample. A 30-item scale was developed in order to review the interest and awareness levels of the teacher candidates, which was intended for determination of the department and class/grade levels of teacher candidates, by benefitting from similar studies by Dinc, Erdil, Kece, and Erhan Metin (2012) on interest and awareness levels of the teacher candidates about the historical and cultural monuments related to local history, and which consisted of 2 diagnostic questions, 1 open-ended question, and 3-point Likert questions, 10 for revealing interest and 17 for revealing awareness. The data from the applied scale was converted into digital (numerical) data by analyzing with SPSS package program. The open-ended question was construed with content analysis. According to the findings of the study, the interest and awareness levels about the historical and cultural monuments located in Sinop did not vary against the gender and department while a significant difference was observed on favor of the males and social sciences teacher candidates in numerical proposition. It was seen that there was a parallelism between the interest and awareness levels, and that the higher the interest levels, the higher the awareness levels for the teacher candidates.